Interaction between salicylic acid and polyamines and their possible roles in tomato hardening processes - Szepesi, Ágnes (Acta Biologica Szegediensis, 2011)
Long-term pre-treatment of tomato plants with low concentration of salicylic acid can induce abiotic stress tolerance by activating enzymatic and non-enzymatic antioxidant defense system. Changes of antioxidant defense system and catabolism of polyamines in tomato (Solanum lycopersicum) plants were investigated. Our results suggest that by affecting the polyamine catabolism salicylic acid can contribute to plant abiotic stress tolerance.